2021
DOI: 10.1253/circj.cj-20-0909
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Functional Decline in Activities of Daily Living at Discharge in Patients After Cardiovascular Surgery

Abstract: Background: This study aimed to investigate the trajectory of functional recovery of activities of daily living (ADL) from the time of admission up to hospital discharge, and explored which preoperative and postoperative variables were independently associated with functional decline in ADL at discharge of patients after cardiovascular surgery. Methods and Results:In this observational study, we evaluated ADL preoperatively and at discharge using the Functional Independence Measure (FIM) in patients after card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…These findings are consistent with the national registry of Korea, which showed that 49% of patients were physically inactive after heart valve surgery [ 9 ], with 39% only becoming inactive after surgery. Japanese researchers found that 18% of patients undergoing cardiovascular surgery experienced a decrease in the activity of daily living (ADL) score at discharge [ 12 ]. Three months after surgery, a functional decrease in ADL was observed in 45% of patients aged 65–79 years and in 56% aged 80 years and older.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with the national registry of Korea, which showed that 49% of patients were physically inactive after heart valve surgery [ 9 ], with 39% only becoming inactive after surgery. Japanese researchers found that 18% of patients undergoing cardiovascular surgery experienced a decrease in the activity of daily living (ADL) score at discharge [ 12 ]. Three months after surgery, a functional decrease in ADL was observed in 45% of patients aged 65–79 years and in 56% aged 80 years and older.…”
Section: Discussionmentioning
confidence: 99%
“…When assessing preoperative factors determining postoperative functional status in older age groups, it was shown that low baseline gait speed and cognitive impairment were predictors of a decrease in ADL after surgery [ 12 ]. In a study by Radi B. et al, the distance of 6MWT at discharge after CABG was 314 ± 76 m, and that after valvular surgery was 328 ± 71 m. The 6MWT distance was significantly associated with gender, age, diabetic status, height and presence of atrial fibrillation in patients after CABG and with gender, age and atrial fibrillation in patients undergoing valve surgery [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HAD was defined as a score of ≤5 (requiring monitoring and preparation by a caregiver) on any one of the FIM subitems at discharge compared to preoperatively 21) .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to physical functions, such as muscle strength, various functional components, including dexterity and cognitive function, are associated with basic ADL [30]; however, these functional assessments were not performed in this study.…”
Section: Limitationsmentioning
confidence: 99%